TOPICAL APPLICATION OF WOUND DRESSINGS IN EARLY SURGICAL TREATMENT OF BURNS ON BORDER COURSE CHILDREN - S. B. Bogdanov; O. N. Afaunova; R. G. Babichev (Медицинский вестник Юга России, 2016)
Purpose: to prove the relevance of the application of wound dressings with early surgical treatment of borderline burns on the extremities in children.Materials and Methods: the core group patients with borderline burns on the extremities who were treated by early surgical treatment with the use of wound dressings, the comparison group patients with borderline burns on the legs, were treated with conservative method (ligation using wound coverings).Results: the study showed the advantage of early surgical treatment of borderline burns on the extremities in children with the use of wound dressings to the local conservative treatment of burns data.Summary: implementation of early surgical treatment with the use of wound dressings allows you to «cure the patient in a single operation», which significantly reduces the complexity of the treatment process, reduces the number of dressings, including reducing the amount of use of the wound surface and the dressing, reduces treatment time, improves the quality of life during treatment.